Love and Romance in Britain, 1918 - 1970
XII, 260 p.
Keywords: The new histories of love and romance offered within this edited collection illustrate the many changes, but also the surprising continuities in understandings of love, romance, affection, intimacy and sex from the First World War until the beginning of the Women's Liberation movement.